The Alignment of Tax Accounting with Financial Accounting: An Analytical Study of the Impact of Tax Policies on Financial Reporting - Alkinani, Hussein Hatem Abd Ali; ALjanaby, Ali Nadhim Mahdi; Rashed, Arshed Makki (South Asian Journal of Social Sciences and Humanities, 2025)
This study examines the relation between tax accounting and financial accounting and analyzes the effect of tax policies and financial reports prepared by companies. The study aims to understand the extent of overlap or discrepancy between the two accounting systems, and the impact of tax and financial accounting on the financial reports adopted in the preparation of financial statements. This paper utilised a sample of 116 companies listed on the stock market and used the Stata program to analyze secondary data. This study found a important and positive association among tax accounting and financial accounting, with tax policies and financial reporting. Tax policies directly impact on the content and credibility of financial reports, as some companies tend to manipulate estimates to reduce their tax burden. The existence of significant variation among the results of tax accounting and financial accounting leads to a decrease in transparency for investors.